Surgeon decision‐making for management of positive sentinel lymph nodes in the post‐Multicenter Selective Lymphadenectomy Trial II era: A survey study. Issue 2 (1st December 2020) - Hui, Jane Yuet Ching; Burke, Erin; Broman, Kristy K.; Marmor, Schelomo; Jensen, Eric; Tuttle, Todd M.; Zager, Jonathan S.
Abstract: Background and Objectives: Completion lymph node dissection (CLND) did not improve melanoma‐specific survival for patients with sentinel lymph node (SLN)‐positive melanoma in the second Multicenter Selective Lymphadenectomy Trial (MSLT‐II). We assessed surgeons' awareness of MSLT‐II and its impact on CLND recommendations. Methods: An anonymous online cross‐sectional survey of the Society of Surgical Oncology membership evaluated surgeon thresholds in offering CLND using patient scenarios and clinicopathologic characteristics ranking. Results: Of the 2881 e‐mails delivered, 146 surgeons (5.1%) completed all seven scenarios. Most (129 of 131, 98%) were aware of MSLT‐II and 125 (95%) found it practice‐changing. Specifically, 52% (65 of 125) always, 40% usually, 6% rarely, and 3% never offered CLND before MSLT‐II. Meanwhile, 4% always, 9% usually, 78% rarely, and 8% never offer CLND now, after MSLT‐II ( p < .0001). The most important clinicopathologic factors in determining CLND recommendations were extracapsular extension, number of positive SLN, and SLN tumor deposit size, while primary tumor mitotic index and nodal basin location were the least important. Surgical oncology fellowship training, melanoma patient volume, and academic center practice also influenced CLND recommendations. Conclusions: Most surgeon respondents are aware of MSLT‐II, but its application in practice varies according to several clinicopathologic and surgeon factors.